On the effect of financial education on financial literacy: evidence from a sample of college students. (5th July 2020) - Brugiavini, Agar; Cavapozzi, Danilo; Padula, Mario; Pettinicchi, Yuri
Abstract: Based on a sample of university students, we provide evidence that a small-scale training intervention has both a statistically and economically significant effect on subjective and objective assessments of financial knowledge. We also show that the intervention increases self-assessed more than actual financial knowledge. The intervention consists of measuring financial literacy before and after a small on-line course and is administered through an on-line platform.